1999
DOI: 10.1159/000026586
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters, Neuroendocrine Correlates of Sensation-Seeking Temperament in Normal Humans

Abstract: Correlations between sensation-seeking (SS) personality dimension and plasma concentrations of norepinephrine (NE), epinephrine, and NE-dependent testosterone (T), cortisol and prolactin (PRL) were studied in 74 physically and psychologically healthy male volunteers, in order to see whether or not the noradrenergic system is involved in the modulation of this personality trait. Novelty-seeking scores by the Temperament and Character Inventory and SS scores on a Visual Analog Scale were positively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 42 publications
3
46
2
2
Order By: Relevance
“…Low levels of cerebrospinal fluid cortisol found in high sensation seekers provide further evidence that cortisol levels are related to sensation seeking. Gerra et al (1999) found a positive correlation between aggression and cortisol but not between novelty seeking and cortisol.…”
Section: Cortisolmentioning
confidence: 80%
See 2 more Smart Citations
“…Low levels of cerebrospinal fluid cortisol found in high sensation seekers provide further evidence that cortisol levels are related to sensation seeking. Gerra et al (1999) found a positive correlation between aggression and cortisol but not between novelty seeking and cortisol.…”
Section: Cortisolmentioning
confidence: 80%
“…Also, high levels of testosterone are correlated with many aspects of sensation seeking. Gerra et al (1999) found that testosterone is positively correlated with novelty seeking, sensation-seeking, and aggression and that testosterone decreases with age. Dabbs and Morris (1990) showed that antisocial behaviors, such as delinquency, substance use/abuse, and multiple sexual partners, are associated with testosterone levels.…”
Section: Testosteronementioning
confidence: 96%
See 1 more Smart Citation
“…The norm on the mental rotation task in the study of Hooven et al may also be the reason for the lack of correlations between testosterone and the intercept. Testosterone has been reported to have a positive correlation with a sensation-seeking score (Gerra et al, 1999); sensation seeking is a personal aspect of the willingness to take risks (Zuckerman, 1996). The norm on our mental rotation task may have repressed risk-taking in high-T subjects.…”
Section: Discussionmentioning
confidence: 92%
“…Novelty seeking behavior observed in this test situation was then compared to novelty seeking discerned in a previous study of the same monkeys (Parker et al 2004) to examine cross-situational consistency in the expression of this behavior. We also investigated whether novelty seeking is associated with differences in cerebrospinal fluid (CSF) measures of various neurochemicals, as studies of humans and animals have linked novelty seeking to monoamines (Bardo et al 1996;Gerra et al 1999;Sara et al 1995;Zuckerman 1985) and stress-related neuropeptides (Kabbaj et al 2000;Thorsell et al 2006). We therefore examined relationships between novelty seeking and CSF levels of the serotonin metabolite 5-hydroxyindoleacetic acid (5HIAA), the dopamine metabolite homovanillic acid (HVA), the norepinephrine metabolite 3-methoxy-4-hydroxyphenylethylene glycol (MHPG), and the neuropeptide corticotrophin-releasing factor (CRF).…”
Section: Introductionmentioning
confidence: 99%